The importance of access to knowledge for technological progress in the Industrial Revolution - Erik Hornung; Julius Koschnick; Francesco Cinnirella (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Sustained technological progress was at the heart of the Industrial Revolution. This column argues that access to knowledge was crucial for innovation and technological diffusion during this period. Inventors and entrepreneurs needed access to useful knowledge to generate new ideas and continue innovating. Such access was provided by the 'economic societies' – associations of individuals interested in improving the local economy. These societies became drivers of knowledge diffusion and innovation.
Keywords: 330